Intergluteal Cleft Eccrine Porocarcinoma with Metastasis to Inguinal Region and Lung: Case Report and Review of the Literature - Ricardo Fernández-Ferreira; Gabriela Alvarado-Luna; Daniel Motola-Kuba; Ileana Mackinney-Novelo; Eduardo Emir Cervera-Ceballos; Román Segura-Rivera (Case Reports in Oncology, 2020)
Eccrine porocarcinoma (EPC) is an infrequent cutaneous neoplasm, and was described in 1963 by Pinkus and Mehregan. It is a rare type of skin tumor (0.005–0.01% of all skin tumors). Less than 300 cases have been described in the entire world medical literature. To our knowledge, no case of intergluteal cleft EPC has been reported in the literature in English and Spanish to date, so this would be the first reported case of such pathology. Metastatic EPC is less frequent, since only <10% of metastatic type have been reported and the rest as localized disease. The primary treatment of choice is surgical wide local excision of the tumor with histological confirmation of tumor-free margins. Prognosis is difficult to determine because of the rarity of EPC and the variations in natural history. There are no data to support the use of adjuvant chemotherapy or radiotherapy, and there are currently no agreed criteria to define patients at high risk of relapse. We present a 67-year-old man with intergluteal cleft eccrine tumor by biopsy. Metastasis to left inguinal region and lung was reported by contrasted abdominal and chest computed tomography. He started chemotherapy based on etoposide, vincristine, carboplatin. A review of pertinent literature is provided.